Improving the Performance of Zinc Oxide Photocatalysts for Phenol Degradation through Addition of Lanthanum Species - Wynona Agatha Nimpoeno; Hendrik Oktendy Lintang; Leny Yuliati (Jurnal Kimia Sains dan Aplikasi, 2020)
One green approach to degrade organic pollutants, such as phenol, is through the photocatalytic reaction. Despite having large band gap energy, which is enough for phenol degradation, zinc oxide (ZnO) has low photocatalytic efficiency. In this study, ZnO was modified by lanthanum (La) species, and the improved photocatalytic activity was confirmed for degradation of phenol under visible and ultraviolet (UV) light irradiation. The ZnO and its modified photocatalysts were prepared by the hydrothermal method in the absence and presence of La species (0.01‒2 wt%). X-ray diffraction (XRD) patterns showed that the addition of La did not disturb the structure of ZnO, but slightly decreased the crystallite size. While the La addition up to 1 wt% did not affect the optical properties of the ZnO, the addition of 2 wt% La slightly red-shifted the absorption band edge of the ZnO. The Fourier-transform infrared (FT-IR) spectra showed La oxide formation observed at 515-540 cm-1 after 2 wt% La addition. Fluorescence emission spectra revealed that synthesized ZnO has oxygen vacancies at 558 nm, and the presence of 1 wt% La did not significantly affect the emission intensity. The photocatalytic activity of ZnO was influenced by the La addition, where the best performance was obtained on the ZnO with 1 wt% La. This study demonstrated that the optimum amount of La species could increase the performance of the ZnO.